Penerapan Inhalasi Sederhana Menggunakan Minyak Kayu Putih Untuk Meningkatkan Bersihan Jalan Nafas Pada Anak Dengan Ispa Di Wilayah Kerja Kelurahan Ponorogo RT 07 Tahun 2025 - Seva, Putri; Sari, Rena Putri; Rahim, Rika; Ulfa, Marlina; Rossita, Taufianie; Rohani, Tuti; Azissah, Danur (Jurnal Gotong Royong, 2025)
Acute respiratory infections are caused by viruses or bacteria. The disease begins with a fever accompanied by one or more symptoms: sore throat or painful swallowing, runny nose, dry cough or phlegm. If the immune defense in the respiratory tract is weakened, this can increase the risk of more serious bacterial infections, such as sinusitis or otitis media. Medical care that can be provided in case of ARI is symptomatic. In addition to medical care, additional therapeutic care can also be given to patients with ARI. One of the complementary therapies that can be given to patients with ARI is simple inhalation of eucalyptus oil. The design of the scientific articles uses a case study model. The subjects used were two children with ARI. Data analysis was done using descriptive analysis. The results of the application showed that after the application of a simple inhalation of eucalyptus oil, the clearance of the subject's airways was again effective, which was marked by a decrease in RR frequency, lack of accumulation of secretions, and a decrease in crackle noise. Mothers who have children with ARI should be able to do or apply a simple inhalation like the one done by the author to try to thin the mucus